2012
DOI: 10.1177/0907568212445225
|View full text |Cite
|
Sign up to set email alerts
|

Two sides of intensive parenting: Present and future dimensions in contemporary relations between parents and children in Spain

Abstract: The objective of this article is to identify and analyse discourses in Spain on intensive parenting in the context of the changes that have taken place in relations between parents and their children in contemporary societies. To do this, the author analyses the discourses from 16 indepth interviews carried out with parents and from 14 focus groups of 11-and 12-year-old children. The article makes a distinction between two analytical dimensions of intensive parenting: intensive parenting for the future, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 14 publications
1
5
0
1
Order By: Relevance
“…In conclusion, the maternal parenting typology developed through this study provided useful information about cultural specificities in socialization practices in Portugal and Spain. The results presented here support the growing body of empirical research, which outlines how parenting practices depend on cultural backgrounds [1,[18][19][20][21]31,65,66]. The description of the parental socialization styles characteristic of each country, due to their cultural influence, has implications for interventions.…”
Section: Discussionsupporting
confidence: 71%
“…In conclusion, the maternal parenting typology developed through this study provided useful information about cultural specificities in socialization practices in Portugal and Spain. The results presented here support the growing body of empirical research, which outlines how parenting practices depend on cultural backgrounds [1,[18][19][20][21]31,65,66]. The description of the parental socialization styles characteristic of each country, due to their cultural influence, has implications for interventions.…”
Section: Discussionsupporting
confidence: 71%
“…These discrepancies in the results seem to show the influence of culture on the relationship between parental socialization and psychosocial adjustment in adolescence, suggesting that the relationship between parenting styles and adolescent adjustment and well-being varies depending on the ethnic, socioeconomic or cultural context (Chao 1994;Espino, 2013;Garcia & Gracia, 2009Kazemi et al, 2010) and, therefore, the optimal parenting style will depend on the cultural environment in which parent-child relationships would generally develop (Berns, 2011;Sigelman & Rider, 2012;Weiten, Dunn, & Hammer, 2012;White & Schnurr, 2012). It has been suggested that people adjust better and are more satisfied in environments that match their attitudes, values, and experiences (Swanson & Fouad, 1999).…”
Section: Introductionmentioning
confidence: 89%
“…Estas discrepancias en los resultados parecen revelar la influencia de la cultura en la relación entre la socialización parental y el ajuste psicosocial de los adolescentes, lo que sugiere que la relación entre los estilos parentales y el ajuste y bienestar de los adolescentes varía según el contexto étnico, socioeconómico o cultural (Chao 1994;Espino, 2013;García y Gracia, 2009Kazemi et al, 2010) y, por lo tanto, el estilo parental óptimo dependerá del entorno cultural en el que las relaciones entre padres e hijos se desarrollen (Berns, 2011;Sigelman y Rider, 2012;Weiten, Dunn, y Hammer, 2012;Blanco y Schnurr, 2012). En este sentido, se ha sugerido que las personas se adaptan mejor y están más satisfechas en ambientes que respondan a sus actitudes, valores y experiencias (Swanson y Fouad, 1999); por ejemplo, dado que las familias de minorías étnicas pobres tienen más probabilidades de vivir en comunidades peligrosas, la parentalidad autoritaria puede no ser tan perjudicial e incluso puede conllevar algunos beneficios protectores para estos contextos peligrosos (Furstenberg, Cook, Eccles, Elder, y Sameroff, 1999).…”
Section: Introductionunclassified
“…The Spanish culture has been characterized as being horizontal collectivist, where parents understand the individual self as part of the family self and emphasize the use of affection and involvement in children's socialization [78][79][80]. However, parenting is particularly concerned about children's safety and physical and emotional well-being, and multiple forms of control appear to be justified and considered necessary for children's security [81]. Education is crucial for Spanish families to optimize children's future possibilities [81].…”
Section: A Cross-cultural View Of Parentingmentioning
confidence: 99%